Value co-creation in multinational enterprises’ services marketing at the bottom-of-the-pyramid markets - Leposky, Tiina; Arslan, Ahmad; Dikova, Desislava (Palgrave Macmillan, Cham, 2019)
This book chapter addresses determinants of value creation by multinational enterprises (MNEs) in the still largely neglected research context of bottom of the pyramid (BoP) markets. Consisting of consumers living below the poverty line, BoP markets exhibit significantly different characteristics compared to the affluent developed or the aspirational emerging markets. Dealing with a wide range of diversity within a market where it is difficult to obtain reliable, generalisable information means that MNEs tend to face challenges upon entering them. Yet, the potential demand offered by BoP markets cannot be ignored and MNE’s have shown increasingly that they are willing to innovate market-specific approaches to cater to BoP needs. We discuss the applicability of service-dominant (S-D) logic in subsistence context and identify commitment to the market, strategic CSR, and service quality as key firm-level determinants of effective service marketing in BoP markets. We further identify social trust, technological outreach and performance orientation characteristics in target BoP market as key country-level determinants. Finally, the book chapter offers a number of academic and managerial implications.
Keywords: BOP markets; service-dominant logic; multinational enterprises; value creation; fi=Kansainvälinen liiketoiminta|en=International Business|